A new technique for convergence theorem of fixed point problem of quasi-nonexpansive mapping - Kanyarat Cheawchan (2018)
© 2015, Cheawchan et al. For the purpose of this paper, we use the method different from the relaxed extragradient method for finding a common element of the set of fixed points of a quasi-nonexpansive mapping, the set of solutions of equilibrium problems, and the set of solutions of a modified system of variational inequalities without demiclosed condition of W and Wω:=(1−ω)I+ωW, where W is a quasi-nonexpansive mapping and (Formula presented.) in the framework of Hilbert space. By using our main result, we obtain a strong convergence theorem involving a finite family of nonspreading mappings and another corollary. Moreover, we give a numerical example to encourage our main theorem.